The Development of Wine Tourism in Atypical Wine Regions: the Challenge of Multistakeholder Cooperation? - Vos, Katleen (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
In the last decades, worldwide wine tourism has been steadily progressing and has grown substantially as a research object. Several academic papers treat strategies for development and management of wine tourism. This paper aims to describe recent trends in wine tourism, and more specifically, the development of wine tourism in atypical wine regions. Therefore, it synthesises the key findings from the second UNWTO wine tourism conference. Furthermore, it argues that the successful development of wine tourism is not an exact science. Emerging wine destinations often have many difficulties to overcome. Using literature review and case studies, it explores the possibilities to create successful destinations and highlights the importance of co-operation, co-creation within networks and creativity to create value for wine tourism destinations.